SEKULARISASI ISLAM SEBAGAI ETIKA UNIVERSAL : (Telaah Pemikiran Nurkholis Madjid) - Nawi, Asnawi Hidayatullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2025)
This study examines Nurkholis Madjid’s views on Islamic civilization in Indonesia. Cak Nur is a phenomenal yet controversial thinker whose ideas are enlightening and thought-provoking. The objectives of this paper are, first, to analyze Cak Nur’s intellectual development. Second, to analyze Cak Nur’s Islamic ideas. Third, to understand his ideas in the context of Indonesian Islamic civilization. This research is library research using historical, sociological, anthropological, and theological approaches, as well as content analysis. The results of this research show that, first, Cak Nur’s intellectual development cannot be separated from his experiences and education; his family’s existence greatly influenced the formation of his thinking. Second, in understanding Cak Nur’s Islamic ideas, the researcher used several approaches, including the substance approach, postmodern epistemology, and inductive empiricism. Third, in reconstructing his ideas, the concept of secularization seeks to free society from the purification or sacralization of things that are not in their proper place (desacralization), so that humans can understand and manage worldly life objectively. Secularization encourages society’s progress towards modernization through rationalization, as a tangible manifestation of Islam’s command that humans use reason and science to understand the laws of nature. In addition, Cak Nur seeks to reinforce Islamic values as a universal moral foundation that can contribute to national progress. Education is a means of shaping and creating quality human resources. Thus, Paramadina University has become a scientific laboratory that emphasizes rationality, openness, and ethical values that can shape a civilized generation.